Effects of automated short-term incomplete milking during peak- to mid-lactation on milk production, udder health, and selected metabolic parameters in dairy cows - Robin Joest; Morteza H. Ghaffari; Karl-Heinz Südekum; Ute Müller (Journal of Dairy Science, 2025)
ABSTRACT: This study investigated the effects of automated short-term incomplete milking (IM) during peak- to mid-lactation on milk production, udder health, and selected metabolic parameters in multiparous Holstein cows. Forty-six cows (94 ± 47 DIM) were randomly assigned to the complete milking treatment (COMP; n = 23, 95 ± 49 DIM, lactation number 3.0 ± 1.3) or the incomplete milking treatment (INCL; n = 23, 93 ± 46 DIM, lactation number 2.6 ± 0.8). In INCL cows, IM was implemented using specialized software that precisely controlled milk withdrawal. Concentrate allocation was dynamically adjusted based on milk yield and DIM via transponder-controlled stations. All cows had ad libitum access to a partial mixed ration and water via automated weighing troughs and bowls. The IM protocol included a gradual reduction phase (first IM phase: 9% daily reduction to ∼40% over 5.5 d), followed by 3 complete milkings, and a constant reduction phase (second IM phase: 40% reduction over 5.5 d). No clinical signs of mastitis or mastitis-relevant bacteria were observed, confirming udder health. In the week prior to IM, milk yield (reference milk yield, REF) did not differ between treatments, with INCL cows achieving between 26 and 59 kg/d. Compared to REF, the milk yield of the INCL cows decreased by 19% (32.7 ± 1.54 kg/d) on the first day after the first IM phase and by 24% (30.7 ± 1.54 kg/d) on the first day after the second IM phase. After cessation of IM, milk yield increased again by 19% within 2 wk and stabilized further at the REF level. Compared to the COMP cows, milk fat content of the INCL cows decreased by 21% and 43% with the onset of the first and second IM phases. Concentrate intake of INCL cows decreased by 65% from 5.4 ± 0.52 kg/d at the beginning of IM to 1.9 ± 0.39 kg/d at the end of IM due to the feed-to-yield feeding system, reflecting lower energy requirements, and increased thereafter. Udder health indicators remained stable during IM. In the INCL cows that completed the trial, SCC were consistently below mastitis thresholds and no relevant pathogens were detected. Milk leakage occurred exclusively in INCL cows during IM, but did not compromise udder health. Serum nonesterified fatty acid concentrations decreased by 63% and 58% during the first IM and second IM phases, respectively, indicating reduced lipid mobilization. Concurrently, IGF-1 concentrations increased by 30% and 28% during the respective phases, indicating metabolic adaptations to the reduced energy demand. In summary, automated short-term IM performed on dairy cows in peak- to mid-lactation using specialized software was successful in temporarily reducing milk production and lactation-induced metabolic load without negatively affecting udder health or long-term performance.